THE IMPACT OF MACROECONOMIC FACTORS ON COMPETITION POLICY EFFECTIVENESS WITHIN EUROPEAN UNION - Dragoi Ionut (Annals of the University of Oradea: Economic Science, 2012)
In the last decades, more and more countries have enacted competition laws, understanding the importance of this process in providing a normal functioning of the economy. Analyzing competition policy effectiveness is important not only because of the recent extent of the phenomenon, but also because of the impact of competition policy effectiveness on economic development and, in the current economic climate, on the economic recovery process. For this reason, quantitative evaluation for competition policy effectiveness became very useful as data handling and understanding the whole phenomenon are easier this way and an international perspective is provided. This was made possible by various international institutions that have created a system of aggregated indicators for the evaluation of competition law enforcement and competition advocacy (perceived effectiveness). The purpose of our research is to identify the macroeconomic factors that influence the effectiveness of competition law implementation within the European Union Member States. We have tasted the influence of 13 macroeconomic, using panel data methodology and data from the last four years. We obtained ÃŸ coefficients statistically significant only for 11 of them. The results are consistent with prior analyzed studies and economic logic: positive influence from market division, intensity of local competition, ethical behavior of firms, strength of auditing and reporting standards, efficiency of legal framework in settling disputes, protection of minority shareholdersâ€™ interests, public trust of politicians, economic dimension and market size and negative influence from corruption level and diversion of public funds. Based on the achieved results we can perform an analysis of principal components leading to causal space reduction with minimal information loss and without informational redundancy, creating the premises for building a model that explains competition policy effectiveness through macroeconomic factors.